2004
DOI: 10.1021/ja048669j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Delocalization in Discotic Liquid Crystals:  A Joint Experimental and Theoretical Study

Abstract: Discotic liquid crystals emerge as very attractive materials for organic-based (opto)electronics as they allow efficient charge and energy transport along self-organized molecular columns. Here, angle-resolved photoelectron spectroscopy (ARUPS) is used to investigate the electronic structure and supramolecular organization of the discotic molecule, hexakis(hexylthio)diquinoxalino[2,3-a:2',3'-c]phenazine, deposited on graphite. The ARUPS data reveal significant changes in the electronic properties when going fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 59 publications
4
98
0
1
Order By: Relevance
“…[45] Hence, integrating the above discussions, the strong cofacial π-π stacking of PDINH molecules along the long axis of its nanoplate would enable effective long-range band-like π-electron delocalization, [46] resulting in an enhancement of electronic coupling [39] and charge mobility. [47,48] Band-like electronic energy level structure similar to inorganic semiconductor due to orbital overlaps between PDINHmolecular units can be obtained by the self-assembled PDINH supramolecular system. Monomeric PDINH molecules own discrete HOMO and LUMO levels, whereas π-stacked PDINH assemblies were reported to have band-like electronic structures with certain bandwidths for valence and conduction bands based on the intermolecular transfer integrals of the HOMOs and LUMOs.…”
Section: Doi: 101002/adma201601168mentioning
confidence: 99%
“…[45] Hence, integrating the above discussions, the strong cofacial π-π stacking of PDINH molecules along the long axis of its nanoplate would enable effective long-range band-like π-electron delocalization, [46] resulting in an enhancement of electronic coupling [39] and charge mobility. [47,48] Band-like electronic energy level structure similar to inorganic semiconductor due to orbital overlaps between PDINHmolecular units can be obtained by the self-assembled PDINH supramolecular system. Monomeric PDINH molecules own discrete HOMO and LUMO levels, whereas π-stacked PDINH assemblies were reported to have band-like electronic structures with certain bandwidths for valence and conduction bands based on the intermolecular transfer integrals of the HOMOs and LUMOs.…”
Section: Doi: 101002/adma201601168mentioning
confidence: 99%
“…Additional theoretical studies that attempt to determine the role of the surface dipole have also been reported. [1,19,22,47] Six fluorinated benzylPAs were synthesized and characterized ( Fig. 1).…”
mentioning
confidence: 99%
“…This type of packing is also in line with previously reported spectroscopic studies on thin films of a similar azatriphenylene-based compound, i.e., hexakis(hexylthio)diquinoxalino[2,3-a:2′,3′-c]phenazine, adsorbed on HOPG. [34] Even though a slight tilting of the molecules during growth cannot be excluded from consideration, a structural transition of the Stransky-Krastanov type within the film, such that the molecules of the undermost layers are oriented parallel to the substrate surface whereas the outermost layers have a different azimuthal order, can be ruled out. As a matter of fact an overlayer was observed on films of similar thickness prepared from dichlorobenzene solutions; SFM phase imaging for such samples revealed a multilayer formation characterized by a different molecular packing during the growth (image not shown).…”
mentioning
confidence: 99%